If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(2t + -2) + 7t = 4t + -7 Reorder the terms: -5(-2 + 2t) + 7t = 4t + -7 (-2 * -5 + 2t * -5) + 7t = 4t + -7 (10 + -10t) + 7t = 4t + -7 Combine like terms: -10t + 7t = -3t 10 + -3t = 4t + -7 Reorder the terms: 10 + -3t = -7 + 4t Solving 10 + -3t = -7 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. 10 + -3t + -4t = -7 + 4t + -4t Combine like terms: -3t + -4t = -7t 10 + -7t = -7 + 4t + -4t Combine like terms: 4t + -4t = 0 10 + -7t = -7 + 0 10 + -7t = -7 Add '-10' to each side of the equation. 10 + -10 + -7t = -7 + -10 Combine like terms: 10 + -10 = 0 0 + -7t = -7 + -10 -7t = -7 + -10 Combine like terms: -7 + -10 = -17 -7t = -17 Divide each side by '-7'. t = 2.428571429 Simplifying t = 2.428571429
| 11(12-y)=110 | | 63=7(20-w) | | 12x^5+18x^3-8x^2-12=0 | | 4(8-b)=8 | | 7(8-c)=49 | | 12=4(6-u) | | 3b+6=-2b+7 | | 8X-4=6x | | 8y-7=y-4 | | 4a+12=-6a-13 | | =7-4i | | 8x+12=27x+1 | | 19=55-4q | | 12q+14=86 | | 111-9q=12 | | 4z/7-3=8 | | 4=100-8q | | 8q+39=63 | | 12x+44=9x+54 | | 3(3s+9)=81 | | 3a^2+1=2-2a | | 4/2*5-(9-6) | | 6(2l+6)=120 | | 8x+12=7x+35 | | 14=32-6x | | 4/5x-1/2=3/4x | | 3.8m-4.2=-1.4(4m+4) | | (u-4)*7=42 | | (q-4)*2=18 | | 4/x=6/8 | | 11-3a-3=2+a | | s*5+45=115 |